Delirium en cuidados paliativos oncológicos: revisión - Porta, Josep; Serrano, Gala; González, Jesús; Sánchez, Daniel; Tuca, Albert; Gómez-batiste, Xavier (Psicooncología, 2004)
We review some aspects related with the physiopathology, epidemiology, diagnosis and management of delirium, centred in patients with advanced and terminal cancer. It is offered a comprehensive and practical overview of this clinical situation frequently under diagnosticated, specially in the case of patients with far-advanced cancer, in whom it is specially frequent and reversible quite often out the last days of life. We emphasize an interdisplinary approach including family as key in diagnosis and treatment. Pharmacological treatment is up dated and some future line of work are mentioned.